TFEB and TFE3 are novel components of the integrated stress response - Martina, José A (EMBO J, 2016)
To reestablish homeostasis and mitigate stress, cells must activate a series of adaptive intracellular signaling pathways. The participation of the transcription factors TFEB and TFE3 in cellular adaptation to starvation is well established. Here, we show that TFEB and TFE3 also play an important role in the cellular response to ER stress. Treatment with ER stressors causes translocation of TFEB and TFE3 to the nucleus in a process that is dependent on PERK and calcineurin but not on mTORC1. Activated TFEB and TFE3 enhance cellular response to stress by inducing direct transcriptional upregulation of ATF4 and other UPR genes. Under conditions of prolonged ER stress, TFEB and TFE3 contribute to cell death, thus revealing an unexpected role for these proteins in controlling cell fate. This work evidences a broader role of TFEB and TFE3 in the cellular response to stress than previously anticipated and reveals an integrated cooperation between different cellular stress pathways.